Does Federalism Affect E-Government in Germany? - Florian Bartholomae; Chang Woon Nam; Peter Steinhoff (Center for Economic Studies and ifo Institute (CESifo), 2023)
International comparisons show that the reasons why e-government development in Germany does not occupy the desired "top spot" in rankings lie primarily in the inadequate provision of online services with little corresponding user orientation. In order to provide better and faster public services in Germany, the Online Access Act was introduced in 2017, which stipulates that the federal, state and local governments must provide 575 services electronically via administrative portals by 2022. However, this deadline has not been met. This study suggests that Germany's federal political structure is significant and that swift and successful implementation of e-government systems in the future will require additional energy, willingness and effort for systematic, comprehensive and intensive coordination between the various levels of government. This applies both to the development of digital solutions for public services and to the reuse of "one-for-all" services already provided for their broad availability across states and municipalities.
Keywords: H40; H77; O38; 330; federalism; e-government; digitalization; public services; Germany